Common terms for rare epilepsies: Synonyms, associated terms, and links to structured vocabularies. Issue 1 (29th January 2018) - Grinspan, Zachary M.; Tian, Niu; Yozawitz, Elissa G.; McGoldrick, Patricia E.; Wolf, Steven M.; McDonough, Tiffani L.; Nelson, Aaron; Hafeez, Baria; Johnson, Stephen B.; Hesdorffer, Dale C.
Summary: Identifying individuals with rare epilepsy syndromes in electronic data sources is difficult, in part because of missing codes in the International Classification of Diseases (ICD) system. Our objectives were the following: (1) to describe the representation of rare epilepsies in other medical vocabularies, to identify gaps; and (2) to compile synonyms and associated terms for rare epilepsies, to facilitate text and natural language processing tools for cohort identification and population‐based surveillance. We describe the representation of 33 epilepsies in 3 vocabularies: Orphanet, SNOMED‐CT, and UMLS‐Metathesaurus. We compiled terms via 2 surveys, correspondence with parent advocates, and review of web resources and standard vocabularies. UMLS‐Metathesaurus had entries for all 33 epilepsies, Orphanet 32, and SNOMED‐CT 25. The vocabularies had redundancies and missing phenotypes. Emerging epilepsies ( SCN2A‐, SCN8A‐, KCNQ2‐, SLC13A5‐, and SYNGAP ‐related epilepsies) were underrepresented. Survey and correspondence respondents included 160 providers, 375 caregivers, and 11 advocacy group leaders. Each epilepsy syndrome had a median of 15 (range 6–28) synonyms. Nineteen had associated terms, with a median of 4 (range 1–41). We conclude that medical vocabularies should fill gaps in representation of rare epilepsies to improve their value for epilepsy research. We encourage epilepsy researchers to use this resource to develop tools to identify individuals with rare epilepsies in electronic data sources.